Configuring Real-Time Event Processing of Api Gateway with Aws and Websocket Api’s - Sarat Dyuthi, Kachiraju Sri (Journal of Informatics Education and Research, 2024)
This monitor explores how to leverage AWS API Gateway's WebSocket APIs for building real-time event processing systems. Unlike traditional HTTP-based APIs, WebSocket APIs allow bidirectional communication, enabling instant data exchange between clients and servers. This setup is ideal for applications that require low-latency interactions, such as chat applications, IoT monitoring, gaming, and live notifications. By configuring API Gateway's WebSocket integration with AWS services like Lambda and DynamoDB, developers can create responsive and scalable event-driven architectures. The document also covers strategies for managing connection states, handling errors, and ensuring secure access, offering a complete framework for real-time data processing in AWS environments. Configuring real-time event processing with AWS API Gateway and WebSocket APIs enables dynamic, bidirectional communication between clients and servers, facilitating instant data transmission. “Unlike traditional REST APIs, WebSocket APIs allow for continuous, persistent connections, making them ideal for applications that require real-time updates, such as chat applications, gaming platforms, financial tickers, and IoT systems. AWS API Gateway provides a fully managed WebSocket solution that simplifies setup, scaling, and management of real-time APIs. By integrating WebSocket APIs with AWS Lambda, DynamoDB, or Amazon Kinesis, developers can process events in real time, store data, or trigger workflows based on incoming messages. This approach not only reduces latency but also enhances application responsiveness and scalability, leveraging AWS’s serverless architecture to handle high volumes of real-time events efficiently.